Optical film and optical laminate
By employing polymers with higher glass transition temperatures and controlled heat set processes, the micro-wrinkling issues in optical laminated bodies are mitigated, enhancing inter-layer peeling resistance and stability under high temperatures.
Patent Information
- Application Number
- JP2024192548
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-05-23
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2040-05-20
AI Technical Summary
Conventional optical laminated bodies used in display applications suffer from micro-wrinkling phenomena due to high temperatures, characterized by non-parallel adjacent surfaces in multilayer films, which increase shrinkage rates and reduce inter-layer peeling resistance.
The use of polymers with higher glass transition temperatures for low refractive index layers and specific adhesive selection to reduce micro-wrinkling, along with controlled heat set processes and layer thicknesses to manage shrinkage rates and improve inter-layer peeling resistance.
This approach effectively reduces micro-wrinkling and maintains inter-layer peeling resistance in optical laminated bodies, even under high temperature exposure, ensuring stable performance in display applications.
Smart Images

Figure 2025016663000001_ABST
Abstract
Description
[Background technology]
[0001] A polarizer stack can include an absorbing polarizer and a reflective polarizer bonded together. Such a polarizer stack can be used in display applications. Summary of the Invention
[0002] In some embodiments of the present disclosure, an optical stack is provided that includes a linear absorbing polarizer and a reflective polarizer disposed on and bonded to the linear absorbing polarizer. For substantially normal incidence light and for at least a first wavelength in the visible wavelength range spanning from about 420 nm to about 650 nm, the reflective polarizer has at least 60% light reflectance for a first polarization state and at least 60% light transmittance for an orthogonal second polarization state, and the linear absorbing polarizer has at least 60% light absorptance for the first polarization state and at least 60% light transmittance for the second polarization state. When heated at 105 degrees Celsius for 15 minutes, the difference in shrinkage between the reflective polarizer and the linear absorbing polarizer along the first polarization state and the second polarization state is greater than about zero and greater than about 0.2%, respectively. The reflective polarizer includes a plurality of alternating first and second polymer layers, where the first polymer layer has an average in-plane refractive index less than the second polymer layer, at least for a first wavelength, and the first polymer layer has a glass transition temperature of at least 107 degrees Celsius.
[0003] In some aspects of the present disclosure, an integrally formed optical film is provided. The integrally formed optical film includes a plurality of alternating first and second polymer layers, a total of at least 50, disposed between two opposite outermost polymer layers. Each of the first and second polymer layers is less than about 400 nm thick, and each outermost polymer layer is greater than about 500 nm thick. The first polymer layer has a glass transition temperature of at least 107 degrees Celsius and an average in-plane refractive index less than that of the second polymer layer. The minimum average peel strength between two portions of the integrally formed optical film is greater than about 0.4 N / cm, and each of the two portions includes one of the outermost polymer layers. In some embodiments, the optical stack includes a linear absorbing polarizer and an integrally formed optical film disposed on and bonded to the linear absorbing polarizer. [Brief description of the drawings]
[0004] [Figure 1] FIG. 2 is a schematic cross-sectional view of an optical laminate. [Diagram 2] FIG. 2 is a schematic diagram of the pass axis of a reflective polarizer and the pass axis of a linear absorbing polarizer. [Diagram 3] FIG. 2 is a schematic cross-sectional view of an optical member. [Figure 4] FIG. 1 is a schematic cross-sectional view of an optical film. [Diagram 5] FIG. 1 is a schematic diagram of a peel test. [Figure 6] 1 is a plot showing the layer thickness profile of a reflective polarizer. [Figure 7] 7 is a plot of transmission versus wavelength for the reflective polarizer of FIG. 6. [Figure 8] 1 is a plot showing the layer thickness profile of another reflective polarizer. [Figure 9] 9 is a plot of transmission versus wavelength for the reflective polarizer of FIG. 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0005] In the following description, reference is made to the accompanying drawings, which form a part hereof, and in which various embodiments are shown by way of illustration. The drawings are not necessarily to scale. It is to be understood that other embodiments are contemplated and may be made without departing from the scope or spirit of the specification. Accordingly, the following detailed description is not to be construed in a limiting sense.
[0006] Optical stacks including an absorbing polarizer and an optical film and / or a reflective polarizer are useful in various display applications. For example, the inner polarizer (the polarizer facing away from the viewer) in a liquid crystal display (LCD) may include an optical stack including a reflective polarizer facing the backlight and an absorbing polarizer facing the display panel. Polarizer stacks and their use in display applications are reviewed, for example, in U.S. Patent No. 6,025,897 (Weber et al.).
[0007] A problem with using optical stacks having absorbing polarizers and conventional reflective polarizers in displays is the phenomenon of micro-wrinkling, which refers to corrugation / buckling in the layers of the film. Such micro-wrinkling can occur during lamination of the optical stack to a component or can occur over time. For example, the optical stacks may be used in automotive applications (e.g., LCD displays in automobiles), where the optical stacks may be exposed to high temperatures that can cause micro-wrinkling. Micro-wrinkling is characterized by adjacent surfaces or interfaces of the multilayer film not being parallel to each other. For example, as described in PCT Application WO 2017 / 205106 (Stover et al.) and corresponding US Patent Application Serial No. 16 / 301106, micro-wrinkling can be reduced by increasing the shrinkage of the reflective polarizer film, thereby avoiding the formation of compressive stresses in the reflective polarizer film due to shrinkage of the absorbing polarizer when exposed to high temperatures.
[0008] Multilayer optical films (e.g., reflective polarizer films) typically include alternating high and low refractive index layers. In accordance with the present specification, it has been found that microwrinkles can be reduced by selecting a polymer for the low refractive index layer that has a higher glass transition temperature than the conventional polymer selected for the low refractive index layer. Traditionally, it has been believed that the low refractive index layer should have a relatively low glass transition temperature (e.g., 105 degrees Celsius or less) in order for a multilayer film to have sufficient delamination resistance or peel strength between adjacent layers. However, it has now been found that using a low refractive index layer with a higher glass transition temperature can provide acceptable delamination resistance and result in reduced microwrinkles. It has also been found that the adhesive used to bond the multilayer optical film to the absorbing polarizer can be selected to reduce microwrinkles. For example, it has been found that an adhesive with a low storage modulus and / or a high tan δ can reduce microwrinkles. Any combination of selecting the relative shrinkage of the reflective polarizer or optical film and the absorbing polarizer, selecting the glass transition temperature of the low refractive index layer, or selecting an adhesive can be used to reduce microwrinkles.
[0009] 1 is a schematic cross-sectional view of an optical stack 100 including a linear absorbing polarizer 110 and an optical film and / or reflective polarizer 110 disposed on and bonded to the linear absorbing polarizer 120. In the illustrated embodiment, the optical film and / or reflective polarizer 110 and the linear absorbing polarizer 120 are bonded together with an adhesive 130. In some embodiments, the optical film and / or reflective polarizer 110 is an integrally formed optical film. In some embodiments, the integrally formed optical film is a reflective polarizer having a pass axis that is substantially aligned with the pass axis of the linear absorbing polarizer.
[0010] 2 is a schematic diagram of a pass axis 112 of a reflective polarizer and a pass axis 122 of a linear absorbing polarizer. The angle θ between the pass axis 112 and the pass axis 122 is shown. The pass axes may be described as substantially aligned, for example, if the angle is less than about 30 degrees. In some embodiments, the angle θ is less than about 30 degrees, or less than about 10 degrees, or less than about 5 degrees, or less than about 3 degrees.
[0011] In some embodiments, the optical stack 100 includes a reflective polarizer 110 and a linear absorbing polarizer 120 bonded together with an adhesive 130, the adhesive 130 having a storage modulus G' at 105 degrees Celsius of less than about 10 kPa and a loss modulus G" at 105 degrees Celsius such that the ratio of the loss modulus G" to the storage modulus G' (tan δ) is at least about 0.4, or at least about 0.5, or at least about 0.6. In some such embodiments, or in other embodiments, the adhesive 130 has a storage modulus G' at 105 degrees Celsius of less than about 8 kPa. It has been found that using an adhesive with a low storage modulus (e.g., less than about 10 kPa, or less than about 8 kPa) and / or a high tan δ (at least about 0.4, or at least about 0.5, or at least about 0.6) reduces microwrinkles in the optical stack. The elastic modulus G' and elastic modulus G" can be determined, for example, by dynamic mechanical analysis. The elastic modulus G' and the elastic modulus G" are determined at a frequency of 1 Hz unless otherwise indicated. The elastic modulus can be determined, for example, according to the ASTM D4065-12 test standard.
[0012] In some embodiments, when heated to 105 degrees Celsius for 15 minutes, the difference in shrinkage between the reflective polarizer 110 and the linear absorbing polarizer 120 along the orthogonal first and second polarization states (e.g., along directions parallel to the first and second polarization states 215 and 219 shown in FIG. 3 ) is greater than about zero and greater than about 0.2%, respectively (e.g., greater than −0.01% and greater than 0.18%, respectively, or greater than 0% and greater than 0.2%, respectively, or greater than 0.01% and greater than 0.22%, respectively). For example, the linear absorbing polarizer 120 may have shrinkage of 0.1% and 0.3% along the pass and block axes, and the reflective polarizer has shrinkage of 0.3% and 0.6% along the pass and block axes, such that the difference in shrinkage between the reflective and absorbing polarizer along the pass and block axes is 0.2% and 0.3%, respectively. In some embodiments, the difference in shrinkage between the reflective polarizer 110 and the linear absorbing polarizer 120 along the second polarization state is greater than about 0.25%, or greater than about 0.3%. In some embodiments, the difference in shrinkage between the reflective polarizer 110 and the linear absorbing polarizer 120 along the first polarization state is greater than about 0.05%, or greater than about 0.1%, or greater than about 0.15%. The difference in shrinkage can be less than 5%, or less than 3%, or less than 1% along each polarization state. Having a difference in shrinkage in these ranges has been found to result in reduced microwrinkling of the optical stack, for example, during lamination of the optical stack to other components or aging at high temperatures. The difference in shrinkage can be controlled by controlling the shrinkage of the optical film and / or the reflective polarizer 110, as further described elsewhere herein.
[0013] 3 is a schematic cross-sectional view of an optical element 250, which may correspond to, for example, the optical film 110 or the linear absorbing polarizer 120. The optical element 250 can be one or more of a linear absorbing polarizer, an optical film, a reflective polarizer, or a plurality of alternating first and second polymer layers. A substantially normal (e.g., within 30 degrees, or within 20 degrees, or within 10 degrees, or within 5 degrees of normal) incident light 213 having a first wavelength λ1 and having a first polarization state 215 is shown generally. A portion 233 of the incident light 213 is reflected (optical reflectance x incident energy), a portion 253 of the incident light 213 (shown diagrammatically by a dashed line without an arrow) is absorbed (optical absorptance x incident energy), and a portion 243 of the incident light 213 is transmitted (optical transmittance x incident energy). A substantially normally incident light 217 having a first wavelength λ1 and a second polarization state 219 orthogonal to the first polarization state 215 is shown diagrammatically. A portion 237 of the incident light 217 is reflected (optical reflectance x incident energy), a portion 257 of the incident light 217 is absorbed (optical absorptance x incident energy), and a portion 247 of the incident light 217 is transmitted (optical transmittance x incident energy).
[0014] In some embodiments, for substantially normally incident light and for at least a first wavelength in the visible wavelength range spanning from about 420 nm to about 650 nm, the reflective polarizer has at least 60% optical reflectance for the first polarization state 215 and at least 60% optical transmission for the orthogonal second polarization state 219, and the linear absorbing polarizer has at least 60% optical absorptance for the first polarization state 215 and at least 60% optical transmission for the second polarization state 219. In some embodiments, the reflective polarizer includes a plurality of alternating first and second polymer layers. In some embodiments, for substantially normally incident light and for at least a first wavelength, the plurality of alternating first and second polymer layers have greater than about 80% optical reflectance for the first polarization state 215, greater than about 85% optical transmission for the second polarization state 219, and less than about 0.1% optical transmission for the first polarization state 215. In some embodiments, the linear absorbing polarizer has a light absorption of at least 70% for the first polarization state 215 and a light transmission of at least 70% for the second polarization state 219 .
[0015] Multilayer optical films are known that provide desirable transmission and / or reflection properties, at least in part, through an arrangement of microlayers having different refractive indices. Such optical films have been demonstrated, for example, by coextrusion of alternating polymer layers, casting the layers through a film die onto a chill roll, and then stretching the cast web. See, for example, U.S. Patent Nos. 3,610,729 (Rogers), 4,446,305 (Rogers et al.), 4,540,623 (Im et al.), 5,448,404 (Schrenk et al.), 5,882,774 (Jonza et al.), 6,157,490 (Wheatley et al.), 6,783,349 (Neavin et al.), and 9,279,921 (Kivel et al.), and International Application Publication No. 2018 / 163009 (Haag et al.). In these polymeric multilayer optical films, polymeric materials can be used primarily or exclusively in making the individual layers. Such films are compatible with mass production processes and can be made as large sheet and roll goods.
[0016] The shrinkage of the multilayer optical film can be controlled by controlling the stress during the cooling of the film after stretching the film. It has generally been found that higher stress during this cooling results in a larger shrinkage. In some embodiments, heat setting is applied after stretching the film. Heat setting can be performed in the final zone of a tenter oven used to orient the film, as described in U.S. Pat. No. 6,827,886 (Neavin et al.). Typically, such a heat setting process is used to reduce or minimize the shrinkage of the film when heat is subsequently applied to the film. If it is desired to minimize the subsequent shrinkage of the film, the heat setting temperature can be set to the highest temperature that does not result in film breakage in the tenter, and the film can be relaxed in the transverse direction near the heat setting zone, which reduces the tension in the film. Higher shrinkage, especially in the machine direction (typically along the pass axis if the optical film is a reflective polarizer), can be achieved by reducing the heat setting temperature, reducing the duration of the heat setting process for a given heat setting temperature, and / or eliminating the heat setting step. Higher shrinkage, especially in the transverse direction (typically along the block axis when the optical film is a reflective polarizer), can be achieved by reducing the relaxation of the film in the block direction. This can be done, for example, by adjusting the spacing between the tenter rails after heat setting. Reducing this spacing is often referred to as toe-in. The effect of heat setting temperature and toe-in on film shrinkage is described, for example, in U.S. Patent Application No. 6,797,396 (Liu et al.). Thus, by controlling the heat setting and toe-in conditions, desired shrinkage in the transverse and machine directions can be achieved when the optical film is heated at 105 degrees Celsius for 15 minutes. Optical shrinkage can be determined, for example, according to ASTM D2732-14 test standard "Standard Test Method for Unrestrained Linear Thermal Shrinkage of Plastic Film and Sheeting".
[0017] FIG. 4 is a schematic cross-sectional view of an optical film 310, which may be a reflective polarizer, including a plurality of alternating first and second polymer layers 361 and 362 disposed between opposite outermost layers 366 and 368 of the optical film 310. The optical film 310 may be an integrally formed optical film, and the outermost layers 366 and 368 may be polymer layers. In some embodiments, the first polymer layer 361 has a smaller average in-plane refractive index (average of the refractive indices along two orthogonal in-plane directions, such as the refractive indices along orthogonal first and second polarization states) than the second polymer layer 362. For example, the second polymer layer 362 may be an oriented layer having a larger refractive index along the first in-plane direction and a smaller refractive index along the second in-plane direction, and the first polymer layer 361 may have substantially the same refractive index along each of the first and second in-plane directions, which is substantially equal to the refractive index of the second polymer layer along the second in-plane direction. The refractive index may be specified, for example, at a first wavelength λ1 in Figure 3. If no wavelength is specified otherwise, the refractive index may be understood to be the refractive index determined at a wavelength of 532 nm. In-plane direction refers to the direction in the plane of the film if the film is laid flat, or in the tangent plane of the film if the film is curved.
[0018] In some embodiments, at least the second polymer layer 362 is substantially uniaxially oriented. For example, in some embodiments, the optical film 310 is a substantially uniaxially oriented film and a reflective polarizer having a degree of uniaxiality U of at least 0.7, or at least 0.8, or at least 0.85, where U=(1 / MDDR-1) / (TDDR 1 / 2 -1), where MDDR is defined as the machine direction stretch ratio and TDDR is defined as the transverse direction stretch ratio. Such substantially uniaxially oriented multilayer optical films are described, for example, in U.S. Patent Application Publication No. 2010 / 0254002 (Merrill et al.).
[0019] In some embodiments, each layer in the first polymer layer 361 and the second polymer layer 362 is less than about 500 nm thick, or less than about 400 nm thick, or less than about 300 nm thick, or less than about 250 nm thick. The thicknesses of the first polymer layer 361 and the second polymer layer 362 can be selected to provide a desired reflectance for a given wavelength of light (e.g., the total optical thickness of a pair of adjacent layers can be selected to be half the given wavelength). The thicknesses of the first polymer layer 361 and the second polymer layer 362 can be varied across the thickness of the optical film to provide a desired reflectance over a given wavelength range (e.g., over about 450 nm to about 650 nm, or about 420 nm to about 650 nm, or about 400 nm to about 700 nm).
[0020] The total number of first polymer layers 361 and second polymer layers 362 may be substantially greater than that shown generally in FIG. 4. In some embodiments, the plurality of alternating first polymer layers 361 and second polymer layers 362 totals at least 50 layers (e.g., 100-500 layers total) and is disposed between opposing outermost polymer layers 366 and 368, each of the first polymer layers 361 and second polymer layers 362 being less than about 400 nm thick and each of the outermost polymer layers 366 and 368 being greater than about 500 nm thick. In some embodiments, the plurality of alternating first polymer layers 361 and second polymer layers 361 of the optical film 310 are disposed between opposing outermost layers 366 and 368 of the optical film 310, each of the outermost layers 366, 368 having a thickness of about 0.5 microns to about 5 microns. In some embodiments, each of the outermost polymer layer 366 and the outermost polymer layer 368 is less than about 2 micrometers thick, or less than about 1.5 micrometers thick, or less than 1 micrometer thick. It has been found that by using outermost layers having such thicknesses, the delamination resistance of the optical film can be improved.
[0021] In some embodiments, for substantially normally incident light in a predetermined wavelength range, the optical film 300, or the plurality of alternating first polymer layers 361 and second polymer layers 362, has an average light reflectance for a first polarization state of greater than about 80%, an average light transmittance for an orthogonal second polarization state of greater than about 85%, and an average light transmittance for the first polarization state of less than about 0.2% or less than about 0.1%. Optical films having such transmittances and reflectances are described, for example, in International Patent Publication WO 2018 / 163009 (Haag et al.).
[0022] The optical film or reflective polarizer herein may be integrally formed. As used herein, a first element "integrally formed" with a second element means that the first element and the second element are manufactured together, rather than being manufactured separately and then subsequently bonded. Integral formed includes manufacturing the first element followed by manufacturing the second element on the first element. An optical film comprising multiple layers is integrally formed when the layers are manufactured together (e.g., combined as a melt stream and then cast on a chill roll to form a cast film, which is then oriented) rather than being manufactured separately and then subsequently bonded. The integrally formed optical film or reflective polarizer may include one or more packets of alternating polymer layers, each of the alternating polymer layers within each packet being less than about 400 nm thick. A layer thicker than about 500 nm may separate adjacent packets, and / or a layer thicker than about 500 nm may be disposed on the outermost surface of one or more packets. Such a layer can be a protective boundary layer (PBL) that is included to prevent the flow profile in a coextruded web of alternating polymer layers from causing optical defects in the alternating polymer layers.
[0023] In some embodiments, the optical film includes two packets of alternating polymer layers and a plurality (e.g., at least three, or 3-20) of thinner (e.g., less than 400 nm thick, or less than 300 nm thick) PBLs disposed between the two packets, which has been found to improve delamination resistance between adjacent packets, as further described in commonly owned Provisional Patent Application No. 62 / 852112, filed May 23, 2019, and entitled "MULTILAYER OPTICAL FILM."
[0024] In some embodiments, the first polymer layer 361 has a glass transition temperature of at least 107 degrees Celsius, or at least 109 degrees Celsius, or at least 112 degrees Celsius, or at least 115 degrees Celsius. In some embodiments, the glass transition temperature of the first polymer layer 361 is 125 degrees Celsius or less, or 120 degrees Celsius or less. It has been found that using a first polymer layer 361 having a glass transition temperature in any of these ranges provides acceptable delamination resistance of the optical film 310 and reduces microwrinkles. In some embodiments, the outermost layer 366 and the outermost layer 368 have a glass transition temperature in any of these ranges. In some embodiments, the outermost layer 366 and the outermost layer 368 are formed from the same material as the first polymer layer 361.
[0025] The glass transition temperature can be determined, for example, by differential scanning calorimetry (DSC). For example, ASTM D3418-15 test standard or ASTM E1356-08 (2014) test standard can be used to determine the glass transition temperature by DSC. Alternatively, the glass transition temperature can be determined by dynamic mechanical analysis (DMA). For example, ASTM E1640-18 test standard can be used to determine the glass transition temperature by DMA. A polymer having a desired glass transition temperature can be formed by blending different polymers having different glass transition temperatures in a ratio that results in the desired glass transition temperature and / or by including different segments in a copolymer in a ratio that results in the desired glass transition temperature. For example, a blend of polycarbonate and copolyester can result in a desired range of glass transition temperatures. In some embodiments, the low refractive index layer (e.g., first polymer layer 361) is formed from a blend of polycarbonate, PETG (a copolyester of polyethylene terephthalate (PET) and cyclohexane dimethanol used as a glycol modifier, available from Eastman Chemicals, Knoxville, Tenn.), and PCTG (a copolyester of PET and twice the amount of cyclohexane dimethanol used as a glycol modifier, available from Eastman Chemicals, Knoxville, Tenn.). The percentage of polycarbonate used can be selected to provide the desired glass transition temperature. In some embodiments, the high refractive index layer (e.g., second polymer layer 362) is formed from polyethylene naphthalate (PEN) or a PEN / polyethylene terephthalate (PET) copolymer. Other polymeric materials known to be useful in polymeric multilayer optical films may alternatively be used.
[0026] The delamination resistance can be characterized in terms of peel force between portions of the optical film. The delamination resistance can be expressed, for example, in grams / inch (understood to be grams of force per inch) or N / cm. For example, in some embodiments, the minimum average peel strength between two portions of the integrally formed optical film 310 is greater than about 0.4 N / cm (e.g., greater than 0.36 N / cm, or greater than 0.38 N / cm), or greater than about 0.6 N / cm, or greater than about 0.8 N / cm, each of the two portions including one of the outermost polymer layers 366, 368. In some embodiments, the minimum average peel strength is determined using a substantially 90 degree peel test at a peel speed of about 1.5 m / min, and the minimum average peel strength is the minimum of the peel strength averaged over an averaging time of about 5 seconds.
[0027] 5 shows a schematic of a peel test applied to an integrally formed optical film 410, which may correspond to optical film 310, for example. Optical film 410 may be cut into standard sizes for testing (e.g., 1 inch (2.54 cm) wide by 12 inch (30 cm) strips). Double sided tape 458 (e.g., 3M 665 Double Sided Tape available from 3M Company, St. Paul, Minn.) is attached to a plate 455 (e.g., a metal plate) and film 410 is attached to double sided tape 448. Film 410 is scored (e.g., with a razor blade) near an edge of the film along score line 444 that forms an angle α with a major surface of plate 455, e.g., in the range of 20 to 60 degrees, or 30 to 45 degrees. The tape 459 is applied to the film 410 such that the tape 459 covers at least the cut portion of the film 410 and such that a free end 479 of the tape 459 is usable in a peel test. For example, the tape 459 can be an approximately 1.5 inch (4 cm) strip of 3M 396 tape available from 3M Company, St. Paul, Minn. The free end 479 used for gripping during the peel test can be folded over on itself to form a non-adhesive tab (e.g., an approximately ½ inch (1.3 cm) tab). A substantially 90 degree peel test is then performed by peeling from the free end 479. For example, the angle β between the pull direction (shown diagrammatically by the applied force F in FIG. 5) and a direction parallel to the top surface of the plate 455 can be approximately 90 degrees. The peel test is performed at a peel speed (speed of the free edge 479 along the pull direction) ranging from about 1.2 to about 1.8 m / min (e.g., about 1.5 m / min). The peel test may be performed, for example, using an IMASS SP-2000 peel tester (IMASS Inc., Accord, MA). The peel strength is averaged over an averaging time of about 4 to about 6 seconds (e.g., about 5 seconds). The average peel strength may be determined at a single averaging time for each one of multiple samples (e.g., five film samples) or at multiple intervals of averaging time for a single (e.g., longer) sample.The minimum of these average peel strengths is referred to as the minimum average peel strength.
[0028] The peel strength is the peel strength between two portions 434 and 435 of the optical film 410, where each of the two portions 434, 435 includes one of the outermost polymer layers (e.g., outermost layer 366 or outermost layer 368 shown in FIG. 4). For example, during a peel test, the optical film 410 may delaminate at an interface between one of the outermost layers and one of the alternating first and second layers (e.g., first layer 361 and second layer 362), whereby one of the two portions 434, 435 includes the delaminated outermost layer and the other of the two portions 434, 435 includes the remainder of the optical film 410. As another example, the optical film 410 may delaminate at an interface between two internal layers, whereby each of the portions 434 and 435 includes the outermost layer and at least one of the alternating first and second layers. As yet another example, delamination may initiate at an interface between the outermost layer and one of the alternating first and second layers and then propagate into an internal layer of optical film 410, such that each of portions 434 and 435 includes a portion of the internal layer. EXAMPLES
[0029] Peel strength test method Film samples were prepared and cut into 1 inch (2.54 cm) wide by 12 inch (30 cm) wide strips. Double sided tape (3M 665 Double Sided Tape available from 3M Company, St. Paul, MN) was attached to a metal plate and the sample strip was attached to the double sided tape. Excess film was cut from one edge of the plate so that the film was flush with this edge and the other edge was scored by cutting at a sharp angle with a razor blade. One end of an approximately 1.5 inch (4 cm) strip of tape (3M 396 Tape available from 3M Company, St. Paul, MN) was folded over on itself to form a 1 / 2 inch (1.3 cm) non-adhesive tab. The other end of the tape was attached to the scored edge of the film sample. 90 degree peel tests were then performed using an IMASS SP-2000 peel tester (IMASS Inc., Accord, MA) at a peel speed of 60 in / min (1.5 m / min) using an averaging time of 5 seconds. Five strips were tested for each film sample. For the results given in the examples, the minimum value is reported to compare the weakest or lowest force required to delaminate the layers from each other.
[0030] Shrinkage Rate Test Method Shrinkage was determined as outlined in the ASTM D2732-14 testing standard, except an oven was used instead of a constant temperature liquid bath. Samples were conditioned in a dry chamber (<20% RH) for >24 hours prior to testing. Samples were tested at 105°C (oven set point) for 15 minutes.
[0031] Comparative Example C1 A birefringent reflective polarizer optical film was prepared as follows: Two multilayer optical packets were coextruded, each consisting of 325 alternating layers of polyethylene naphthalate (PEN) and a low refractive index isotropic layer, the low refractive index isotropic layer being made of a blend of polycarbonate and copolyester (PC:coPET) with a refractive index of about 1.57, which remained substantially isotropic upon uniaxial orientation, the weight ratio of PC:coPET being about 41% by weight PC and 59% by weight coPET, and having a Tg of 105.8 degrees Celsius. The isotropic material was selected such that after stretching, the refractive index of the isotropic material in the two non-stretched directions remained substantially matched to the refractive index of the birefringent material in the non-stretched direction, and in the stretched direction, there was a substantial mismatch in refractive index between the birefringent and non-birefringent layers. The PEN and PC / coPET polymers were fed from separate extruders to a multilayer coextrusion feedblock where they were combined into two packets of 325 alternating optical layers plus thicker protective boundary layers of PC / coPET on the outside of the stacked optical packets and nine alternating internal protective boundary layers of optical thickness but no coherence between the packets for a total of 661 layers. The multilayer melt was then cast through a film die onto a chill roll in the conventional manner for polyester film and quenched as it was cast. The cast web was then stretched in the transverse direction at a ratio of about 6:1 at a temperature of 320° F. in a parabolic tenter as described in U.S. Pat. No. 6,916,440 (Jackson et al.).
[0032] The layer thickness profile for the optical film of Comparative Example 1 is shown in FIG. 6. The pass and block transmissions at normal incidence were determined and are shown in FIG. 7. The average transmissions from 450 to 650 nm for block and pass polarized light were 0.011% and 86.7%, respectively. The film of Comparative Example 1 had a total thickness of about 58.9 μm as measured by a capacitance gauge. The shrinkage at 105° C. for 15 minutes was about 1.01% in the machine direction (MD) and about 0.15% in the transverse direction (TD). The minimum average peel force was 256.7 g / in.
[0033] A Sanritz 5518 absorbing polarizer containing an adhesive layer was laminated to the optical film using the adhesive on the Sanritz polarizer to provide an optical stack.
[0034] Example 1 A birefringent reflective polarizer optical film was prepared as follows: Two multilayer optical packets were coextruded, each packet having 325 alternating layers of 90 / 10 coPEN, a polymer composed of 90% polyethylene naphthalate (PEN) and 10% polyethylene terephthalate (PET), and a low refractive index isotropic layer made of a blend of polycarbonate and copolyester (PC:coPET) such that the refractive index is about 1.57 and remains substantially isotropic upon uniaxial orientation, the weight ratio of PC:coPET being about 61% PC and 39% coPET by weight, and having a Tg of 116.4 degrees Celsius. The isotropic material was selected so that after stretching, the refractive index of the isotropic material in the two non-stretched directions remained substantially matched to the refractive index of the birefringent material in the non-stretched direction, and there was a substantial mismatch in refractive index between the birefringent and non-birefringent layers in the stretched direction. The PEN and PC / coPET polymers were fed from separate extruders into a multilayer coextrusion feedblock where they were combined into two packets of 325 alternating optical layers, plus thicker protective boundary layers of PC / coPET on the outside of the stacked optical packets, and nine alternating internal protective boundary layers of optical thickness but no coherence between the packets, for a total of 661 layers. The multilayer melt was then cast through a film die onto a chill roll and quenched as it was cast, in the conventional manner for polyester film. The cast web was then stretched in the transverse direction at a ratio of about 6:1 at a temperature of 300° F. in a parabolic tenter as described in US Pat. No. 6,916,440 (Jackson et al.).
[0035] The layer thickness profile for the optical film of Example 1 is shown in FIG. 8. The pass and block transmission at normal incidence was determined and is shown in FIG. 9. The average transmission from 450-650 nm for block and pass polarized light was 0.021% and 89.2%, respectively. The film of Example 1 had a total thickness of about 58.7 μm as measured by a capacitance gauge. The shrinkage at 105° C. for 15 minutes was 0.31% and 0.57% in MD and TD, respectively. The minimum average peel force was 226.9 g / in.
[0036] A Sanritz 5518 absorbing polarizer (available from Sanritz Co., Ltd., Japan) containing an adhesive layer was laminated to the optical film using the adhesive on the Sanritz polarizer to provide an optical stack. The shrinkage of the Sanritz polarizer at 105° C. for 15 minutes was 0.10% and 0.30% along the pass and block axes, respectively.
[0037] Examples 2 to 8 Examples 2-8 were prepared in a manner similar to Example 1, except for the changes shown in Table 1. The glass transition temperature (Tg) of the low index optical (LIO) layer was calculated from the glass transition temperatures of the PC and coPET used in the blend. The loadings of PC and coPET, the calculated Tg, pass and block state shrinkage at 105°C for 15 minutes, the delta pass and block state shrinkage difference between the sample and the Sanritz polarizer at 105°C for 15 minutes, and the minimum average peel force are reported in Table 1. [Table 1]
[0038] Micro Wrinkle Test 3M 8171 adhesive (obtained from 3M Company, St. Paul, Minn.) was laminated to both sides of the optical laminates of Comparative Example C1 and Examples 1-8, which were then laminated to glass slides.
[0039] Two samples from each laminate of Comparative Example C1 and Examples 1-3 were placed in an oven set at 105° C. for 225 hours and then placed in a thermal cycle oven for 20 cycles of 30 minutes at 105° C. to 30 minutes at −40° C. After each oven condition, Comparative Example 1 had microwrinkles and Examples 1-3 had no microwrinkles.
[0040] Two samples from each laminate of Comparative Example C1 and Examples 4-8 were placed in an oven set at 105° C. for 24 hours. After 24 hours, they were removed from the oven, allowed to cool to room temperature, and inspected for microwrinkles. Comparative Example 1 had microwrinkles and Examples 4-8 did not have microwrinkles.
[0041] To test the effect of adhesives between the reflective and absorbing polarizers, various adhesives were used between the reflective polarizer of Comparative Example C1 and the Sanritz 5518 absorbing polarizer. The adhesive on the Sanritz polarizer was used to laminate the optical stack to a glass slide. The samples were placed in an autoclave at 50°C and 0.5 MPa for 20 minutes to ensure good bonding. The bonded samples were placed in an oven set at 105°C for 24 hours. The samples were then removed from the oven, allowed to cool to room temperature, and inspected for microwrinkles. The results are reported in the table below. The adhesives were obtained from 3M Company (St. Paul, MN). The elastic modulus was determined at 105°C using DMA. [Table 2]
[0042] Terms such as "about" will be understood by those of skill in the art in the context in which they are used and described herein. If the use of "about" when applied to a quantity describing the size, amount, and physical properties of a feature is not clear to a person of skill in the art in the context in which they are used and described herein, "about" will be understood to mean within 10 percent of the specified value. If the use of "about" when applied to a difference between a quantity describing the size, amount, and physical properties of a feature is not clear to a person of skill in the art in the context in which they are used and described herein, "about" when applied to the difference will be understood to mean within 10 percent of the quantity having the smaller magnitude. For example, if "about zero" when applied to the difference between a quantity having a value of 0.275 and a quantity having a value of 0.3 is not clear to a person of skill in the art in the context in which they are used and described herein, the difference is about zero because the difference differs from zero by less than 10 percent of 0.275. A quantity given as about a specified value may be exactly the specified value. For example, if it is not clear to a person of ordinary skill in the art, in the context in which it is used and described herein, a quantity having a value of about 1 means that the quantity has a value of 0.9 to 1.1, and means that the value may be 1.
[0043] All references, patents, or patent applications referenced above are hereby incorporated by reference in their entirety. In the event of any inconsistency or contradiction between any portion of the incorporated reference and this application, the information in the foregoing description shall take precedence.
[0044] Descriptions of elements in a figure should be understood to apply equally to corresponding elements in other figures unless otherwise indicated. Although specific embodiments have been illustrated and described herein, those skilled in the art will appreciate that the specific embodiments illustrated and described may be replaced by various alternative and / or equivalent embodiments without departing from the scope of the present disclosure. This application is intended to cover any adaptations or variations of the specific embodiments discussed herein. Accordingly, it is intended that the present disclosure be limited only by the claims and their equivalents.
Claims
1. A linear absorbing polarizer; and a reflective polarizer disposed on and coupled to the linear absorbing polarizer; For substantially normally incident light, and for at least a first wavelength in the visible wavelength range spanning from about 420 nm to about 650 nm, the reflective polarizer has a light reflectance of at least 60% for a first polarization state and a light transmission of at least 60% for an orthogonal second polarization state; the linear absorbing polarizer has an optical absorptance of at least 60% for the first polarization state and an optical transmittance of at least 60% for the second polarization state; when heated to 105 degrees Celsius for 15 minutes, the difference in shrinkage between the reflective polarizer and the linear absorbing polarizer along the first polarization state and the second polarization state is greater than about zero and greater than about 0.2%, respectively; 1. An optical stack, wherein the reflective polarizer comprises a plurality of alternating first and second polymer layers, the first polymer layers having an average in-plane refractive index less than the second polymer layer, at least for the first wavelength, and the first polymer layers having a glass transition temperature of at least 107 degrees Celsius.
2. The optical stack of claim 1 , wherein the first polymer layer has a glass transition temperature of at least 109 degrees Celsius.
3. 10. The optical stack of claim 1, wherein the first polymer layer has a glass transition temperature of at least 115 degrees Celsius.
4. The optical stack of any one of claims 1 to 3, wherein each layer within the first polymer layer and the second polymer layer is less than about 500 nm thick.
5. 5. The optical stack of claim 4, wherein the plurality of alternating first and second polymer layers of the reflective polarizer are disposed between two opposing outermost layers of the reflective polarizer, each outermost layer having a thickness of about 0.5 microns to about 5 microns.
6. The optical stack according to any one of claims 1 to 5, wherein at least the second polymer layer is substantially uniaxially oriented.
7. 7. The optical stack of claim 1, wherein for substantially normally incident light and for at least the first wavelength, the plurality of alternating first and second polymer layers have an optical reflectance for the first polarization state of greater than about 80%, an optical transmittance for the second polarization state of greater than about 85%, and an optical transmittance for the first polarization state of less than about 0.1%.
8. 8. The optical stack of any one of claims 1 to 7, wherein the reflective polarizer and the linear absorbing polarizer are bonded together with an adhesive, the adhesive having a storage modulus G' at 105 degrees Celsius less than about 10 kPa and a loss modulus G" at 105 degrees Celsius such that the ratio of the loss modulus G" to the storage modulus G' is at least about 0.
5.
9. 1. An integrally formed optical film comprising a plurality of alternating first and second polymer layers, a total of at least 50, disposed between two opposing outermost polymer layers, wherein each of the first and second polymer layers is less than about 400 nm thick, and each outermost polymer layer is greater than about 500 nm thick, the first polymer layer has a glass transition temperature of at least 107 degrees Celsius and an average in-plane refractive index less than that of the second polymer layer, and a minimum average peel strength between two portions of the integrally formed optical film is greater than about 0.4 N / cm, and each of the two portions comprises one of the outermost polymer layers.
10. 10. The optical film of claim 9, wherein the minimum average peel strength is greater than about 0.6 N / cm, or greater than about 0.8 N / cm.
11. 11. The optical film of claim 9 or 10, wherein each outermost polymer layer is less than about 2 micrometers thick.
12. 12. The optical film of claim 9, wherein the plurality of alternating first and second polymer layers have a light reflectance of greater than about 80% for a first polarization state, a light transmittance of greater than about 85% for an orthogonal second polarization state, and a light transmittance of less than about 0.1% for the first polarization state for substantially normally incident light and for at least a first wavelength in the visible wavelength range spanning from about 420 nm to about 650 nm.
13. A linear absorbing polarizer; and An optical film according to any one of claims 9 to 12, disposed on the linear absorbing polarizer and bonded to the linear absorbing polarizer; An optical laminate comprising:
14. 14. The optical stack of claim 13, wherein the optical film comprises a reflective polarizer having a pass axis that is substantially aligned with a pass axis of the linear absorbing polarizer.
15. 15. The optical stack of claim 13 or 14, wherein the optical film and the linear absorbing polarizer are bonded together with an adhesive, the adhesive having a storage modulus G' at 105 degrees Celsius of less than about 10 kPa and a loss modulus G" at 105 degrees Celsius such that the ratio of the loss modulus G" to the storage modulus G' is at least about 0.5.
Citation Information
Patent Citations
Modified copolyester and optical film containing modified copolyester
JP2008517139A
Pressure-sensitive adhesive sheet, optical film with pressure-sensitive adhesive layer, and image display device
JP2015030765A
Multilayer optical film, method of making the same, and transaction card having the same
JP2017204000A
Optical film
JP2017521700A
Film roll layer body
JP2018105923A